2022
DOI: 10.1002/acm2.13648
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of imaging performance of a novel helical kVCT for use in image‐guided and adaptive radiotherapy

Abstract: ClearRT helical kVCT imaging for the Radixact helical tomotherapy system recently received FDA approval and is available for clinical use. The system is intended to enhance image fidelity in radiation therapy treatment planning and delivery compared to the prior MV‐based onboard imaging approach. The purpose of this work was to characterize the imaging performance of this system and compare this performance with that of clinical systems used in image‐guided and/or adaptive radiotherapy (ART) or computed tomogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Of the 10 unique protocols previously evaluated, five were reevaluated in this study. The comparison of applicable IQM between this study and Tegtmeier et al [5] is shown in Table 1. Based on these values, the application of the updated reconstruction software resulted in a further reduction in noise by over 20% relative to the previous software for the Thorax and Pelvis anatomy protocols and by over 30% for the head anatomy protocol.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Of the 10 unique protocols previously evaluated, five were reevaluated in this study. The comparison of applicable IQM between this study and Tegtmeier et al [5] is shown in Table 1. Based on these values, the application of the updated reconstruction software resulted in a further reduction in noise by over 20% relative to the previous software for the Thorax and Pelvis anatomy protocols and by over 30% for the head anatomy protocol.…”
Section: Discussionmentioning
confidence: 78%
“…Two recent publications included an analysis of image quality for this system in comparison to CT simulation and other on-board CT systems (cone-beam CT and MVCT) for several image quality metrics [ 4 , 5 ]. These previous studies concluded that this system performed well in comparison to the other systems for IQM important to the implementation of IGRT and ART, as the contrast was consistent with a CT simulator and overall image quality was greatly improved when compared to MVCT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations